2012
DOI: 10.5032/jae.2012.03084
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teacher Demographic and Personal Characteristics on Perceptions of Diversity Inclusion in Agricultural Education Programs

Abstract: Agricultural education teachers’ attitudes about the perceptions of diversity inclusion in their programs are variables that may have a strong influence on the number of students that enroll in agricultural education. This study examines the effect of teachers’ demographic and personal characteristics on their perceptions of the benefits of diversity inclusion, perceived barriers to diversity inclusion, and proposed solutions to increase diversity inclusion in agricultural education programs. Using a web–based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
2
11
0
Order By: Relevance
“…The two urban FFA advisors of this study had difficulty engaging their FFA members beyond the chapter level. These findings echoed those of previous studies (LaVergne, Jones, Larke, & Elbert, 2012;LaVergne et. al., 2011;Roberts et.…”
Section: Discussionsupporting
confidence: 92%
“…The two urban FFA advisors of this study had difficulty engaging their FFA members beyond the chapter level. These findings echoed those of previous studies (LaVergne, Jones, Larke, & Elbert, 2012;LaVergne et. al., 2011;Roberts et.…”
Section: Discussionsupporting
confidence: 92%
“…The issues the National FFA Organization faces regarding diversity and inclusion are complex, and solutions are not completely clear. For example, multiple scholars have pointed to cultural obstacles such as stereotypes, perceptions, and prejudices that have prevented diverse membership within FFA programs (LaVergne et al, 2012;Talbert & Larke, 1995;Warren & Alston, 2007). At the same time, a variety of factors play a role in perceptions influencing a more diverse membership within the FFA that deal not only with students, but also with other stakeholders.…”
Section: Figurementioning
confidence: 99%
“…There is a growing need for research on the diversity and inclusion of social groups within SBAE classrooms beyond basic demographic data collection. In fact, agricultural education literature over the last decade has specifically called for research focused on unpacking recognized diversity and inclusion deficiencies (LaVergne et al, 2012;Talbert & Edwin, 2008;Vincent & Kirby, 2015); deficiencies that has been well-documented within the agricultural education profession for over two decades (Jones & Bowen, 1998;Talbert & Larke, 1995), and have arguably been present since its inception.…”
Section: Introductionmentioning
confidence: 99%
“…Warren and Alston (2007) found that North Carolina agriculture teachers posit that barriers to diversity inclusion include the existence of prejudices and stereotypes, the general perceptions of agriculture, and guidance counselors' efforts to place poor performing students in their courses. LaVergne et al (2012) emphasized that Texas agricultural teachers perceived a lack of role models, ongoing stereotypes, perceptions of agriculture, and acceptance of peers as major barriers to obtaining a diverse program. Teachers are a driving force in setting the tone for local programs, which includes the recruitment and retention of students, influencing peer interactions, and establishing a positive classroom environment (Darling-Hammond & Bransford, 2005).…”
Section: Introductionmentioning
confidence: 99%